Impact of COVID-19 vaccination on symptoms and immune phenotypes in vaccine-naïve individuals with Long COVID - Connor B. Grady; Bornali Bhattacharjee; Julio Silva; Jillian Jaycox; Lik Wee Lee; Valter Silva Monteiro; Mitsuaki Sawano; Daisy Massey; César Caraballo; Jeff R. Gehlhausen; Alexandra Tabachnikova; Tianyang Mao; et al. (Communications Medicine)
Abstract Background The symptomatic and immune responses to COVID-19 vaccination of people with Long COVID are poorly characterized. Methods In this prospective study, we evaluated changes in symptoms and immune responses after COVID-19 vaccination in 16 vaccine-naïve individuals with Long COVID. Surveys were administered before vaccination and at 2, 6, and 12 weeks after receiving the first vaccine dose of the primary series. Simultaneously, SARS-CoV-2-reactive TCR enrichment, SARS-CoV-2-specific antibody responses, antibody responses to other viral and self-antigens, and circulating cytokines were quantified before vaccination and at 6 and 12 weeks after vaccination. Results At 12 weeks post-vaccination, self-reported improved health is seen in 10 out of 16 participants, 3 have no change, and 3 have worse health although 2 report transient improvement after vaccination. One participant reporting worse health was hospitalized twice with chest pain (after each dose). Symptom outcomes are most associated with plasma biosignatures. Higher baseline sIL-6R is associated with symptom improvement, and stably elevated levels of IFN-β and CNTF are associated with no improvement. Significant elevation in SARS-CoV-2-specific TCRs and spike protein-specific IgG are observed at 6 and 12 weeks after vaccination. No changes in reactivities are observed against herpes viruses and self-antigens. Conclusions In this study of 16 people with Long COVID, vaccination is associated with increased SARS-CoV-2 spike protein-specific IgG and T cell expansion in most participants. Specific immune features are associated with symptom change after vaccination and most participants experience improved health or no change following vaccination.